Immune‐Related Adverse Events as a Biomarker in Non‐Melanoma Patients Treated with Programmed Cell Death 1 Inhibitors. (26th June 2017) - Judd, Julia; Zibelman, Matthew; Handorf, Elizabeth; O'Neill, John; Ramamurthy, Chethan; Bentota, Sasini; Doyle, Jamie; Uzzo, Robert G.; Bauman, Jessica; Borghaei, Hossein; Plimack, Elizabeth R.; Mehra, Ranee; et al.
Abstract: Background: The programmed death 1 (PD‐1) checkpoint inhibitors (CKIs) can lead to immune‐related adverse events (irAEs). We sought to evaluate whether the development of irAEs correlates with treatment response in non‐melanoma malignancies. Materials and Methods: We conducted a retrospective study of patients who received anti‐PD‐1 CKI monotherapy at Fox Chase Cancer Center. Endpoints included overall response rate (ORR), time to next therapy or death (TTNTD), and overall survival (OS). Fisher's exact tests and logistic regression models were used to determine the association between irAE incidence and ORR, and Kaplan‐Meier curves with log‐rank tests and Cox regression models were used for the comparison of TTNTD and OS. Results: Between November 2011 and November 2016, 160 patients were treated with >1 dose of an anti‐PD‐1 CKI. Seventy‐three (46%) were treated on a clinical trial. Immune‐related adverse events were noted in 64 patients (40%), with steroids required in 36 (23%). Of the 142 patients evaluable for clinical response, 28 patients (20%) achieved a partial response at first scan. An association between irAEs and ORR was seen in clinical trial patients ( p = .007), but not in non‐trial patients ( p = .13). When controlling for clinical trial participation and cancer type using multivariate analysis, low‐grade irAEs had higher ORR ( p = .017) and longer TTNTD ( p = .008). No association between irAE incidence and OS was seen ( p = .827). Immune‐related adverse events that required steroid treatment were marginally associated with increased TTNTD ( p = .05, hazard ratio 0.62) but were not associated with OS ( p = .13). Conclusion: We demonstrate several positive associations between the development of irAEs and clinical outcomes in non‐melanoma patients treated with PD‐1 CKIs, for which further validation is required. Abstract : Immune checkpoint inhibitors are a novel class of immunotherapeutic agents being used in clinical practice for many advanced malignancies. Checkpoint blockade targeting the programmed cell death 1 receptor or its primary ligand with pembrolizumab, nivolumab, or atezolizumab has received U.S. Food and Drug Administration approval for the treatment ofmetastatic melanoma, non‐small cell lung cancer, renal cell carcinoma, Hodgkin's lymphoma, head and neck squamous cell carcinoma, and urothelial carcinoma. Considering that checkpoint blockade treatments now extend to tumor types beyond melanoma, a study was conducted to evaluate whether the development of immune‐related adverse events correlates with treatment response in other cancer subtypes.